Relationships on Residential Care - Quality of care and perceptions of Warmth/Rejection of children in residential care - Fernández-Baena, Francisco Javier; Fernández-Sánchez, Joanna; Gaitán, Sabina D.; Fernández-Baena, Francisco Javier; Salas-Martínez, María Dolores (My University, 2025)
Residential care remains one of the essential measures for the protection of children and adolescents. This study is part of a larger project examining the quality of care and development of children in residential care. This research analyses the relationship between the warmth or rejection perceived by children from their caregivers and the quality of care. It also analyses whether there are differences in the warmth or rejection perceived depending on the number of young people residing in the care home (≤8 places vs. 20 places). A total of 101 children/adolescents between 9 and 16 years of age and 94 caregivers from 16 protection homes in the province of Malaga (Spain) participated in the study. An ad hoc instrument named EQUAR-Andalucía based on the EQUAR quality standards was created and used to assess the quality of care. Specifically, standards 13 (‘Normalization and Integration’) and 14 (‘Development and Autonomy’) of the children's version and standard 21 (‘Affective and Emotional Needs’) of the caregiver’s version were used.
Keywords: Cuidadores - Aspectos psicológicos - Congresos; Quality of care; Residential Care; Careworkers; Adolescents